The Impact of Foreign Direct Investment (FDI) on Pakistan Exports: An Empirical Analysis - Niaz Ahmed Bhutto; Abdul Khaliq Daudpota; Raja Shahzad; Maria Tabassum; Asma Malik (JISR Management and Social Sciences & Economics, 2008)
Over the last three decades, there have been high inflows of FDI at unprecedented accelerated rates; but the growth of exports has been increasing, however, not at satisfactory level. FDI can affect, directly and indirectly, the exports of hosting country. Using the time series data from 1977 to 2005, a double log model has been used to estimate impact of FDI on exports and results show that the two years lagged FDI has statistical significant positive impact on the current exports of Pakistan. FDI in textile sector, which is backbone of exports, had been very low in this period. The same was the case with other exporting sectors. As a matter of fact, exports do have a significant place in Pakistan, so Government of Pakistan should formulate such economic policies, as relaxation on foreign exchange control, abolishment of technical fee and introduction of the suitable tax relief policy for the foreign investors that attract FDI, especially resource-oriented, in Pakistan.